Costs of Nonoperative Procedures for Knee Osteoarthritis in the Year Prior to Primary Total Knee Arthroplasty. (5th October 2022) - Nin, Darren Z.; Chen, Ya-Wen; Talmo, Carl T.; Hollenbeck, Brian L.; Mattingly, David A.; Niu, Ruijia; Chang, David C.; Smith, Eric L.
Abstract : Background: The convergence of national priorities to reduce health-care costs and deliver high-value care warrants the need to examine health-care utilization. The objective of this study was to describe the costs associated with nonoperative procedures in the 1-year period leading up to primary total knee arthroplasty (TKA). Methods: An observational cohort study was conducted using the IBM Watson Health MarketScan databases. Patients with late-stage knee osteoarthritis (OA) who underwent unilateral, isolated primary TKA from January 1, 2018, to December 31, 2019, were included. The main outcome was the cost of knee OA-related payments for identified nonoperative procedures in the 1-year period before surgery. Nonoperative procedures examined were (1) physical therapy (PT); (2) bracing; (3) intra-articular injections: professional fee, hyaluronic acid (IA-HA), and corticosteroids (IA-CS); (4) medication: nonsteroidal anti-inflammatory drugs (NSAIDs), opioids, and acetaminophen; and (5) knee-specific imaging. Results: The study population included 24, 492 TKA patients with a mean age of 60.4 ± 8.0 years. The average total cost of nonoperative procedures per patient was $1, 355 ± $2, 087. The most common nonoperative treatment prescribed was IA-CS (54.3%). The nonoperative procedure with the highest cost per patient was IA-HA ($1, 019 ± $913 per patient). The total cost of nonoperative procedures was higher among female compared with male patients ($1, 440 ± $2, 159 versus $1, 254 ± $1, 992 per patient; p < 0.01). The highest costs were found for patients in the Northeast ($1, 740 ± $2, 437 per patient). A total of 14, 346 (58.6%) and 7, 831 (32.0%) of the patients had >1 and ≥3 nonoperative treatments, respectively. Conclusions: There is substantial variation in the type and the cost of nonoperative treatment for patients with late-stage OA. Future studies should investigate the effectiveness of nonoperative treatments at different stages of the disease. Level of Evidence: Therapeutic Level III . See Instructions for Authors for a complete description of levels of evidence.